Neuronal Aquaporin 1 Inhibits Amyloidogenesis by Suppressing the Interaction Between Beta-Secretase and Amyloid Precursor Protein. (10th March 2020) - Park, Jinsu; Madan, Meenu; Chigurupati, Srinivasulu; Baek, Seung Hyun; Cho, Yoonsuk; Mughal, Mohamed R; Yu, Amin; Chan, Sic L; Pattisapu, Jogi V; Mattson, Mark P; Jo, Dong-Gyu
Abstract: The accumulation of amyloid-β (Aβ) is a characteristic event in the pathogenesis of Alzheimer's disease (AD). Aquaporin 1 (AQP1) is a membrane water channel protein belonging to the AQP family. AQP1 levels are elevated in the cerebral cortex during the early stages of AD, but the role of AQP1 in AD pathogenesis is unclear. We first determined the expression and distribution of AQP1 in brain tissue samples of AD patients and two AD mouse models (3xTg-AD and 5xFAD). AQP1 accumulation was observed in vulnerable neurons in the cerebral cortex of AD patients, and in neurons affected by the Aβ or tau pathology in the 3xTg-AD and 5xFAD mice. AQP1 levels increased in neurons as aging progressed in the AD mouse models. Stress stimuli increased AQP1 in primary cortical neurons. In response to cellular stress, AQP1 appeared to translocate to endocytic compartments of β- and γ-secretase activities. Ectopic expression of AQP1 in human neuroblastoma cells overexpressing amyloid precussir protein (APP) with the Swedish mutations reduced β-secretase (BACE1)-mediated cleavage of APP and reduced Aβ production without altering the nonamyloidogenic pathway. Conversely, knockdown of AQP1 enhanced BACE1 activity and Aβ production. Immunoprecipitation experiments showed that AQP1 decreased the association of BACE1 with APP. Analysis of a human database showed that the amount of Aβ decreases as the expression of AQP1 increases. These results suggest that the upregulation of AQP1 is an adaptive response of neurons to stress that reduces Aβ production by inhibiting the binding between BACE1 and APP.